The solar cycle effect on the atmosphere as a scintillator for meteor observations - Pellinen-Wannberg, Asta; Murad, Edmond; Broasch, Noah; Häggström, Ingemar; Khayrov, Timur (Proceedings of the International Astronomical Union, 2009)
We discuss using high solar cycle atmospheric conditions as sensors for observing meteors and their properties. High altitude meteor trails (HAMTs) have sometimes been observed with HPLA (High Power Large Aperture) radars. At other times they are not seen. In the absence of systematic studies on this topic, we surmise that the reason might be differing atmospheric conditions during the observations. At EISCAT HAMTs were observed in 1990 and 1991. Very high meteor trails were observed with Israeli L-band radars in 1998, 1999 and 2001.Through the Leonid activity, around the latest perihelion passage of comet Tempel-Tuttle, optical meteors as high as 200 km were reported. This was partly due to new and better observing methods. However, all the reported periods of high altitude meteors seem to correlate with solar cycle maximum. The enhanced atmospheric and ionospheric densities extend the meteoroid interaction range with the atmosphere along its path, offering a better possibility to distinguish differential ablation of the various meteoric constituents. This should be studied during the next solar maximum, due within a few years. Godkänd; 2009; 20140416 (vicbar)